2011
DOI: 10.1044/0161-1461(2011/10-0063)
|View full text |Cite
|
Sign up to set email alerts
|

The Integration of Lexical, Syntactic, and Discourse Features in Bilingual Adolescents' Writing: An Exploratory Approach

Abstract: Similar results across languages implied the potential transfer of writing skills. Overall, students appeared to apply a knowledge-telling strategy to writing rather than strategically planning, composing, and revising their writing. Finally, outcomes highlighted the synergistic relationships among linguistic levels in text composition, indicating a need to address the interaction of vocabulary, morphosyntax, and text-level structures in the instruction and assessment of ELL writing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 25 publications
2
22
0
1
Order By: Relevance
“…Moreover, the level of academic language knowledge needed for grade-level achievement requires an average of five to seven years to attain (Cummins 2013). Previous study on the bilingual writing of this group of students (Danzak 2011) strongly suggested that the lexical, syntactic, and discourse aspects of the academic register in both languages were less well developed, whether they were previously educated in the USA or elsewhere. A question, which merits more refined instructional research to resolve, is whether this gap in the academic register represents differences from monolinguals in how bilinguals manage more complex language and literacy learning, as Geva and Farnia (2012) suggest, in combination with inadequate experience in the analysis and synthesis of word relations in both Spanish and English.…”
Section: Research Implicationsmentioning
confidence: 83%
See 3 more Smart Citations
“…Moreover, the level of academic language knowledge needed for grade-level achievement requires an average of five to seven years to attain (Cummins 2013). Previous study on the bilingual writing of this group of students (Danzak 2011) strongly suggested that the lexical, syntactic, and discourse aspects of the academic register in both languages were less well developed, whether they were previously educated in the USA or elsewhere. A question, which merits more refined instructional research to resolve, is whether this gap in the academic register represents differences from monolinguals in how bilinguals manage more complex language and literacy learning, as Geva and Farnia (2012) suggest, in combination with inadequate experience in the analysis and synthesis of word relations in both Spanish and English.…”
Section: Research Implicationsmentioning
confidence: 83%
“…The data in this study were drawn from a larger, mixed methods investigation of the bilingual writing of Spanish-speaking English learners in middle school (Danzak 2011). For the current inquiry, the students' writing samples were evaluated for spelling error patterns and compared across languages.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Diego participated in a prior mixedmethods study of bilingual narrative and expository writing of Spanish-speaking ELs that took place in his ESOL classroom (Danzak, 2011b(Danzak, , 2011c. Diego was among six of 20 participants randomly selected to serve as focal students in this study.…”
Section: Data Collection: 2008mentioning
confidence: 99%